CaFriend Cafe / Norhadymanshah Lim... [et al.] - Lim, Norhadymanshah; Ujang, Abdul Hadi; Majus, Ellydiah Ezuris; Danny, Pechy Dabora; Peter, Joanna (2013)
CaFriend plans to provide a service that meets the needs and demands of our consumers which is the local people and tourists. Apart from that, CaFriend Cafe also will be participating in opening franchises globally that provides a professional and efficient service. We shall be employing whichever person that wants to work for us regarding of their gender. Only a matter of expertise and experienced is in primary consideration. The positions are Manager, Assistant Manager, Supervisor, Sales Executive, General Worker, Cashier, and Cleaner. Our product focuses on delivering and providing good service for having a repeat customer or loyal customer. Every consumer wants to be treated nicely and neatly so that they will use or consuming our product repeatedly. We tend to sale our product or service accordingly and affordable. There are items that high in price and low in price but our professional and efficient service is a must. Our competitors are the other bakery shop such as Secret Recipe that are located near our cafe. They have their own strength such as their variety types of cakes, cuisine, rolls, and drinks according with their status that well-known to other people. Local people would naturally prefer more to the image of the shop. That is inevitable for every human being. Despite of their strength, they also have the following weaknesses such as the inefficient service that they provide and the availability of their product. However, we notice that there are several opportunity that we can take advantage which are the number of loyal or repeat customer might increasing and opening a new branches plus adding more product such as new cakes and drinks. Nevertheless, we acknowledge that there are several risks involve which are the cost production of the new product may need a big amount of money and maintaining the professional and efficient service is proven difficult.